Electrician's pocket manual / Rex Miller - Miller, Rex 1929- (McGraw-Hill pocket reference, 2000)
This toolbox-sized time-and-trouble saver makes short shrift of all those questions that pop up during your day's work, whether they relate to tools of the trade...standard electrical procedures...working with fiber optics and installing the newest communications equipment...basic math and measurement, including conversion...reading blueprints. It's also loaded with 100 tables and charts, 100 formulas and 300 diagrams. You get safety rules, definitions and abbreviations of electrical units of measurement, and symbols for electrical construction drawings, including the new symbols for electrical drafting now being used in CAD drafting. An appendix even looks at codes, standards and regulations.